Different starting times of α-Tocopherol and γ-Tocotrienol supplementation and tumor marker enzyme activities in-the rat chemically induced with cancer - Makpol, S.; Shamaan, N.A.; Jarien, Z.; Md Top, A.G.; Khalid, B.A.K.; Wan Ngah, W.Z. (Elsevier Science, 1997)
1. α-Tocopherol (α-T) and γ-tocotrienol (γ-T) were supplemented continuously for 8 weeks in the diets of normal rats and rats chemically induced with cancer using diethylnitrosamine (DEN), 2-acetylaminofluorene (AAF) and partial hepatectomy. Hepatocarcinogenesis was followed by determining the plasma γ-glutamyl-transpeptidase (GGT) and alkaline phosphatase (ALP) activities as well as placental glutathione S transferase (PGST) and GGT activities histochemically, at 4-week intervals. 2. Male Rattus norvegicus were supplemented α-T and γ-T at two different doses of 30 and 300 mg/kg diet. The supplementation was started at three different times: simultaneously with DEN administration; 4 weeks; and 8 weeks after DEN administration. 3. Elevation of plasma GGT activities and formation of PGST and GGT positive foci were attenuated significantly (P < 0.05) when α-T and γ-T were supplemented simultaneously with cancer induction. Supplementation begun 4 and 8 weeks after cancer induction did not affect plasma enzyme activities and formation of enzyme positive foci. 4. α-T was more effective than γ-T, and a lower dose of 30 mg/kg was found to be more effective in reducing the severity of hepatocarcinogenesis.